Peranan Warga Gereja dalam Pertumbuhan Gereja - Pujiwati (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
AbstractThe church is not only an organization but also an organism so that the church must grow both inquality and quantity. The church is not only managed by church leaders but all church membershave responsibilities that God has given according to their respective gifts or talents for theirspiritual growth and church growth. Church members play an important role in the growth of thechurch. This is a divine mandate that God celebrates for church members. In this study, the authoruses a qualitative method, namely a literature study to describe the role of church members inchurch growth. By using literature review, the author formulates a useful and useful research.